EFEKTIFITAS LEAFLET TERHADAP PENGETAHUAN DAN MENGATUR POLA MAKAN LANSIA PENDERITA HIPERTENSI DI PUSKESMAS SERASAN KABUPATEN NATUNA - Nurvi Susanti; - Qodariah; Yessi Harnani; Zulmeliza Rasyid (LPPM Universitas Muhammadiyah Riau, 2017)
Hypertension is a disease that is incurable but manageable. Good knowledge about hypertension is one right way to prevent and tackle the problem of hypertension. One way to cope with hypertension is to provide information to the public about how to treat hypertension with leafleat. Recapitulation reports obtained from the Natuna District Health Office in 2014 that consists of 12 districts can be seen the most number of hypertension is highest in district Serasan as many as 753 people and the elderly 46 people. The purpose of this study to determine the effectiveness of the leaflet to the knowledge and diet of elderly patients with hypertension in Natunare regency Serasan district health centers in 2015. The research method is quantitative with quasi experiment. This study was conducted on 12 March 2015 in the Natuna district health centers serasan. Population in this study were all hypertension patients with a total sample of 46 people with sampling by total sampling, the use of computerized data processing and analysis of univariate and bivariate by T test. Bivariate analysis results are known there is a difference between knowledge before and after given leaflets with value p = 0,000 < 0,05, besides there are also differences between respondents diet before and after the given leafleats with the value p = 0,038 < 0,05. The conclusion that the leaflet is effective against knowledge and eating habits elderly patients with hypertension. Serasan district health centers are expected to further improve the Natuna field health promotion services by providing ongoing counseling on a scheduled basis and at least 1 time in a month and multiply media such as posters or leaflet about hypertension as an effort to decrease the incidence of hypertension, especially in the region Natuna regency Serasan district health center.